Development of E-Module Based on Mathematical Literacy Skill in Statistical Materials - Efendi, Shindy Amelia; Haryono, Yulia; Cesaria, Anna (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2024)
This research aims to produce an E-Module with math literacy-based questions that are valid and practical for 10th-grade statistics in SMA Negeri 3 Padang. The type of research conducted is development research using the ADDIE development model. Data analysis techniques include interview analysis, E-Module validation analysis, and E-Module practicality analysis. The results of the research show that mathematics learning using the E-Module, which facilitates mathematical literacy questions, is both valid and practical. Based on the data analysis, it was found that the developed E-Module had a validity score of 92.31%, categorized as highly valid. The final practicality score for teachers was 85%, categorized as highly practical, and the final practicality score for students was 88.26%, also categorized as highly practical.